Outcomes of Arthroscopic Posterior Medial Meniscus Root Repair: Association With Body Mass Index. Issue 3 (1st February 2019) - Brophy, Robert H.; Wojahn, Robert D.; Lillegraven, Olivia; Lamplot, Joseph D.
Abstract : Introduction: The purpose of this study was to assess the association of outcomes from posterior medial meniscus root repairs with patient age, sex, and body mass index (BMI). Methods: Patients who underwent arthroscopic posterior medial meniscus root repair completed the Knee Injury and Osteoarthritis Outcome Score (KOOS) and reported subsequent surgeries. The association of patient factors with subsequent surgery and clinical osteoarthritis (OA) based on the KOOS score was evaluated. Results: Minimum 2-year follow-up was available on 22/25 patients (88%). Two patients (9.1%) had subsequent surgeries, and 10 (45.5%) met the KOOS criteria for OA. A BMI over 35 kg/m 2 was associated with repeat surgery (25% versus 0%; P = 0.049) and clinical OA (75% versus 28.6%; P = 0.035). Conclusion: Although arthroscopic repair of posterior medial root tears has good clinical outcomes and a low rate of subsequent surgery, an elevated BMI level is associated with worse clinical outcomes and a higher rate of subsequent surgery.